Validar una propuesta de la adaptación del framework DevOps de Nagarajan y Overbeek incluyendo prácticas de seguridad para organizaciones financieras - Del Valle Hilacondo, Thelly Raúl (2024)
Financial organizations working with traditional methodologies are interested in adopting an agile way of working that improves the frequency and quality of the software they release, as well as reinforcing security measures in the software development and deployment process. While it is true that there is currently a wide variety of DevOps models, no models oriented towards small financial companies that include security aspects were found in the reviewed literature. Therefore, this study proposes the validation of the adaptation of a model to implement DevOps with security practices in financial companies, based on the model proposed by A.D. Nagarajan and S.J. Overbeek. As part of this study, a survey was applied to 14 professionals related to software development working in a financial company who evaluated the perception of the proposed model in terms of ease of use, intention to use, and perceived usefulness. A analysis of the participants, descriptive analysis, and statistical tests were conducted to evaluate the validity of the perception questionnaire through interitem correlation analysis, convergent and discriminant validation, and Cronbach's alpha reliability test. These results support the reliability and validity of the questionnaire used in this study. Then, the Technology Acceptance Model (TAM) was used as a theoretical framework to analyze the relationship between perception variables using Spearman's linear regression analysis techniques. The results obtained suggest that the proposed model has a positive impact on the frequency of delivery of new releases and the quality of the deliveries. Additionally, an improvement in security measures is perceived when applying the proposed model. After analyzing the information, it is concluded that participants perceive the model as easy to use and show a positive intention to use it, however, they remain unsatisfied with the improvement in security. This translation maintains the meaning and structure of the original Spanish text, conveying the key points about the model's impact, ease of use, and the participants' perceptions regarding security improvements.